A randomized controlled trial of 3 IU Intravenous oxytocin bolus with 7 IU oxytocin infusion versus 10 IU oxytocin intramuscular in the third stage of labor for the prevention of postpartum hemorrhage - Shivakumar Pujeri (BLDE University Journal of Health Sciences, 2020)
Objective: Intravenous oxytocin during vaginal delivery has been rarely used as an intramuscular route or intravenous infusions are preferred. The trial aims to compare low dose Intravenous (IV) bolus 3IU of oxytocin along with 7IU oxytocin infusion to 10IU oxytocin infusion in cesarean section. Materials and Methods: A total of 320 term pregnant women were randomized to either 3IU IV bolus and 7IU infusion of oxytocin or 10IU of IV oxytocin infusion. The difference in pre- and post-delivery haemoglobin levels, tone of the uterus, hemodynamic changes, adverse effects of the drug, need for additional uterotonics and need for blood transfusions were assessed. Results: There were more women who had a drop in the haemoglobin of 3gm/dl in the intramuscular oxytocin group than the IV bolus- infusion group (11%vs 4%), though the difference was not statistically significant. The tone of the uterus was firmer in the IV bolus group at 3 and 5 minutes. There was no significant difference in the hemodynamic changes, adverse effects, need for additional uterotonics or need for blood transfusions. Conclusion: Intravenous bolus of 3IU with 7IU infusion of oxytocin is as safe as and more effective than Intramuscular injection of 10 IU of oxytocin during vaginal delivery for the prevention of postpartum haemorrhage.